2008
DOI: 10.1556/aphysiol.95.2008.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute maximal exercise on lymphocyte subgroups in type 1 diabetes

Abstract: The essential therapy of diabetes mellitus includes medical nutrition therapy (MNT), exercise and medical therapy. Exercise, besides its metabolic effects, has positive influence on the immune system, but some forms of exercise may cause trauma for muscle and skeletal systems, they may also support negative effects on the immune system. Nineteen type 1 diabetic patients (mean age 22.1 +/- 2.8 yrs), followed by Diabetes Outpatient Clinic and twenty age matched male control subjects were included into the study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…In the face of chronic hyperglycaemia (predominantly of more than 10 mmol/L), alterations of several steps of phagocytosis [12–14] including oxidative burst [15, 16] and occasionally abnormalities of selected lymphocyte subpopulations [17] as well as immunoglobulins [18] have been described in both in vivo and in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the face of chronic hyperglycaemia (predominantly of more than 10 mmol/L), alterations of several steps of phagocytosis [12–14] including oxidative burst [15, 16] and occasionally abnormalities of selected lymphocyte subpopulations [17] as well as immunoglobulins [18] have been described in both in vivo and in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies with conflicting results regarding the effect of diabetes mellitus on the immune system. Both in vivo and in vitro studies have demonstrated that chronic hyperglycaemia causes oxidative burst and anomalies in lymphocyte subpopulations and immunoglobulins [49][50][51][52][53][54][55][56] . In a study with diabetic ulcer patients and diabetic controls, no significant difference was detected between the two groups in terms of total leukocyte count.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…It is known that FAs have positive effects on the immune system [46]. Regular aerobic exercises have been shown to increase NK cell numbers and functions, alter CD4 T cells/CD8 T cells ratios, increase the levels of immunoglobulin M (IgM) and IgG, thereby increasing a person's resistance to infections [47,48].…”
Section: Physical Activitymentioning
confidence: 99%